Investment Behavior: The Effects of Overconfidence Bias and Herding Behavior (DEPAN, 2025)
This study analyzes the factors that influence individual investment behavior in Budhanilkantha Municipality, focusing on the psychological aspects that affect decision-making. The research specifically looks at how overconfidence bias and herding behavior impact investment choices, using gender as a moderating variable. The research utilized a cross-sectional design. A structured questionnaire was employed to gather data from 107 participants with diverse occupational backgrounds. The findings indicate a significant positive relationship between overconfidence bias, herding behavior, and investment decisions. Investors who exhibit higher confidence in their knowledge tend to make more frequent investment decisions, and many are also influenced by the opinions and behaviors of their peers. Overconfidence bias was identified as the most influential factor in investment behavior. The study concludes that understanding these psychological influences is vital for individual investors and financial professionals when making informed decisions. This knowledge contributes to market stability and efficiency. The insights gained from this study offer valuable implications for developing investment strategies and enhancing financial literacy initiatives.